Urinary incontinence: prevalence, risk factors, impact on quality of life and treatment seeking behaviour among middle aged women - Agarwal, Brijesh Kumar; Agarwal, Namita (International Surgery Journal, 2017)
Background: Urinary incontinence (UI) is one of the priority health issue recognized by WHO. Urinary incontinence (UI) is defined by the international continence society as "a condition in which involuntary loss of urine is objectively demonstrable and is a social and hygiene problem. It is a common and distressing medical condition severely affecting quality of life (QOL). Urinary incontinence is a common health problem among women, with the prevalence varying from 8-45% in different studies. Methods: This study was based among the population around SRM-IMS, Bareilly. Total 464 women were interviewed out of 2860 total inhabitants. Results: Out of 464, 236 females were selected for this study. 28 women had urinary incontinence. The overall prevalence of urinary incontinence in our study was about 12%. There was significant association of increasing age and presence of urinary incontinence. Urinary incontinence does impact on quality of life of a woman having urinary incontinence. Impact of personal factors do not have much impact on urinary incontinence. 22% women had stress urinary incontinence, 38% had urgency incontinence and 38% had mixed type of urinary incontinence. Conclusions: Various obstetrical factors do contribute to urinary incontinence. Urinary incontinence is a significant health problem in the society leading to restriction in social and sexual activities. Almost 1 in 12 women suffering from urinary incontinence. Simple epidemiological tools such as a questionnaire can unveil the urinary incontinence subjectively. Further efforts are to be done to improve the quality of life and minimizing the urinary incontinence by pursuing them for treatment.